2019
DOI: 10.1186/s12935-019-0989-5
|View full text |Cite
|
Sign up to set email alerts
|

Why are olfactory ensheathing cell tumors so rare?

Abstract: The glial cells of the primary olfactory nervous system, olfactory ensheathing cells (OECs), are unusual in that they rarely form tumors. Only 11 cases, all of which were benign, have been reported to date. In fact, the existence of OEC tumors has been debated as the tumors closely resemble schwannomas (Schwann cell tumors), and there is no definite method for distinguishing the two tumor types. OEC transplantation is a promising therapeutic approach for nervous system injuries, and the fact that OECs are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 158 publications
0
17
0
Order By: Relevance
“…As the turnover of neurons is a normal and continuous process, it is important that an inflammatory environment is not created by the OECs that would otherwise comprise the functioning of the olfactory nerve. Similarly, recruitment of macrophages is not desirable as it would require continual infiltration of macrophages into the olfactory nerve 13,60 . Indeed, rather than attracting macrophages, OECs appear to repel these cells; MIF secretion from both OECs and macrophages have been shown important for this segregation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…As the turnover of neurons is a normal and continuous process, it is important that an inflammatory environment is not created by the OECs that would otherwise comprise the functioning of the olfactory nerve. Similarly, recruitment of macrophages is not desirable as it would require continual infiltration of macrophages into the olfactory nerve 13,60 . Indeed, rather than attracting macrophages, OECs appear to repel these cells; MIF secretion from both OECs and macrophages have been shown important for this segregation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The SCs secrete inflammatory cytokines such as interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-α (TNF-α), and IL-1α (Fregnan et al, 2012) which results in recruitment of macrophages to the site of injury. As hematogenous macrophages enter the injury site later, it is estimated that the initial 40-50% of the debris clearance is performed by SCs along with help from the resident endoneurial macrophages (Perry et al, 1995;Mueller et al, 2003). The exact time of arrival of hematogenous macrophages is unknown.…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
“…The exact time of arrival of hematogenous macrophages is unknown. Previous work in rodents reports macrophage arrival at the lesion site almost 2-3 days after injury, with numbers peaking between day 7 and 14 (Perry et al, 1987;Stoll et al, 1989;Taskinen and Roytta, 1997;Bendszus and Stoll, 2003;Mueller et al, 2003). One study reported the presence of infiltrating macrophages as early as 36 h after mouse sciatic nerve axotomy (Beirowski et al, 2004).…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
See 2 more Smart Citations